Intersecting Interregionalism
XIII, 196 p. 3 illus.
Keywords: Intersecting Interregionalism moves beyond narrow understandings of regions and interregionalism that dominate the research field by focusing on the polymorphous nature of the concepts under study, theoretical advances and the empirical challenges ahead. Written by leading experts in the field, the ultimate aim of the book is to contribute to a more relevant and nuanced comparative research agenda on interregionalism in Europe and elsewhere. The volume is divided into two parts. The first provides an overview of several distinctive theoretical perspectives, with particular emphasis on the dynamic relationship between regions and interregionalism. The second part of the book uncovers the diversity of regional actors and institutions that are engaged in the creation of contemporary interregionalism. The EU is used as an entry point and detailed case studies explore the role of EU member states, the Council, the Commission, the European Parliament and the Court of Justice, in order to map out a patchwork of intersecting interregionalisms around the world.